SELF-ESTEEM LEVELS IN PREGNANT WOMEN BASED ON SOCIOECONOMIC STATUS - Ummi Humaida Arfi; Widia Lestari; Yulia Irvani Dewi (Jurnal SMART Keperawatan, 2024)
Introduction: The level of self-esteem in pregnant women can be influenced by socioeconomic status, where socioeconomic status can be reviewed through family income. Income will help pregnant women in overcoming difficulties that may occur during pregnancy, one example is when pregnant women are required to do routine checks. Objective: The purpose of this study was to determine the level of self-esteem of pregnant women based on socioeconomic status. Methods: This study used a descriptive research design, The sample in this study amounted to 71 respondents, taken using the total sampling technique. Data collected using the Rosenberg Self-esteem scale questionnaire which has been tasted for validity and reliability, The analysis used univariate test. Result: The results obtained from this study indicate that the majority of respondents with low socioeconomic status with moderate self-esteem (52.1%), moderate socioeconomic status with moderate self-esteem (94.4%) and low socioeconomic status with high self-esteem (60%). Conclusion: Socioeconomic status is factor that can change the level of self-esteem of pregnant women.